Uji Efektivitas Patch Transdermal Ekstrak Etanol Kulit Batang Kayu Jawa (Lannea Coromandelica (Houtt.) Merr) Terhadap Luka Sayat Pada Tikus Putih Jantan (Rattus Norvegicus) - Safaruddin; Mike Arum; Sri Wahyuningsih; Rahmahsinar Amin (PT FORMOSA CENDEKIA GLOBAL, 2022)
The bark of Java wood (Lannea coromandelica (Houtt.) Merr) contains secondary metabolites of flavonoids, saponins and tannins that can help the wound healing process. The purpose of this study was to determine the effectiveness of the transdermal patch of ethanolic extract of the bark of Javan bark against cuts in male white rats (Rattus norvegicus). The method, a laboratory experiment using male white rats (Rattus norvegicus) as experimental animals, transdermal patches of Javanese bark extract were tested against cuts on rats. The treatment group consisted of positive control, patch negative control, extract concentration of 3%, 6% and 9%. The treatments were observed for 14 days. The results at concentrations of 3%,6% and 9% indicated the percentage of wound healing. In conclusion, the transdermal patch of ethanolic extract of Javanese bark) at concentrations of 3%, 6% and 9% had effectiveness on wound healing in rats.